Learning for a Better Future Perspectives on Higher Education, Cities, Business & Civil Society - Kearns, Peter (The Centre for Local Economic Development: Topics in Local Development, 2021)
Various international scholars and associates of the PASCAL (Place, Social Capital and Learning Regions) International Observatory (Africa hub), under the auspices of the Centre for Local Economic Development (CENLED) based at the University of Johannesburg (UJ), have contributed chapters in this scholarly book. The book aims to demonstrate how a combination of globalisation, pandemics and the impact of innovation and technologies are driving towards a world in which traditional ideas are being challenged. The book carries forward a dual context and relevance: to South African social, educational, economic and cultural development, and the broader international context and action directed at how lifelong learning for all can be fostered in communities as a foundation for a just, human-centred, sustainable world. The distinctive contribution of this book to the production of a local body of knowledge lies in the symbiotic relationships between these objectives, so that South Africa could serve as a test case in working towards approaches that have a wider international significance.